Sexually transmitted infections in primary health care - Pinto, Valdir Monteiro; Tancredi, Mariza Vono (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Over time, estimates of sexually transmitted infection (STI) cases have been pointing to a higher incidence in developing countries(1), and although the real magnitude of the problem is not known, these infections are possibly among the ten most frequent causes of demand for health services, with health, social, and economic consequences(2). [...]